2019
DOI: 10.1097/md.0000000000015386
|View full text |Cite
|
Sign up to set email alerts
|

The effect of anti-gravity treadmill training for knee osteoarthritis rehabilitation on joint pain, gait, and EMG

Abstract: Introduction: To date, the anti-gravity treadmill (AlterG), as a representative method of Lower body positive pressure (LBPP) treadmills, has been rarely reported for knee osteoarthritis (KOA) rehabilitation. The purpose of this case study was to setup the clinical protocol example for AlterG intervention on KOA and evaluate treatment effectiveness by 3D gait analysis combined with free EMG to explore the kinematic gait parameter changes. Patient concerns: A 65-year-old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Meanwhile, the LBPP treadmill proved useful for reducing pressure across the entire foot in normal subjects while running[ 21 ]. Previous studies have also indicated that the effects of LBPP cause an increase in the reduction of the peak joint force on the knee joint[ 11 ]. Based on this finding, we have reason to infer that the knee pressure on the mechanical chain would be reduced accordingly, which might be crucial for knee OA patients undergoing rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, the LBPP treadmill proved useful for reducing pressure across the entire foot in normal subjects while running[ 21 ]. Previous studies have also indicated that the effects of LBPP cause an increase in the reduction of the peak joint force on the knee joint[ 11 ]. Based on this finding, we have reason to infer that the knee pressure on the mechanical chain would be reduced accordingly, which might be crucial for knee OA patients undergoing rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…The entire training session was supervised by a trained physiotherapist for guidance and safety. The patients in the LBPP group (experimental treatment group) performed an LBPP walking training program (provided using AlterG M320 Antigravity Treadmill, California, USA) for 30 min/session/day, 6 d/week for 2 wk, which was based on our previous study[ 11 ]. The LBPP walking protocol included 20 min walking stage (speed = 1.5–2.0 mph, BW = 65%, Incline = 0%) and 10 min warm-up and cooling down stage at the beginning and ending of the session (Figure 1B ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a case study, knee OA pain was reduced using reduced gravity treadmill walking for 2 weeks. 66 As the knee pain decreased, several biomechanical variables improved, including increased stride length, walking velocity, and flexion-extension excursion during stance. Rectus femoris, semitendinosus, and biceps femoris activation also increased.…”
Section: Knee Pain and Walking Biomechanicsmentioning
confidence: 99%
“…LBPPSS is increasingly used after knee surgery to reduce ground reaction forces during walking and running to facilitate postoperative rehabilitation [20], [21]. It has also been successfully employed in children with cerebral palsy [22].…”
Section: Introductionmentioning
confidence: 99%